A novel role for 14-kDa phosphohistidine phosphatase in lamellipodia formation. Issue 5 (3rd September 2017) - Xu, Anjian; Li, Xiaojin; Li, Siwen; Sun, Lan; Wu, Shanna; Zhang, Bei; Huang, Jian
ABSTRACT: Cell migration involves dynamic regulation of the actin cytoskeleton, which exhibits rapid actin polymerization at the leading edge of migrating cells. This process relies on regulated recruitment of actin nucleators and actin-binding proteins to the leading edge to polymerize new actin filaments. Many of these proteins have been identified, including the actin-related protein (Arp) 2/3 complex, which has emerged as the core player in the initiation of actin polymerization. However, the functional coordination of these proteins is unclear. Previously, we have demonstrated that the 14-kDa phosphohistidine phosphatase (PHP14) is involved in cell migration regulation and affects actin cytoskeleton reorganization. Here, we show that PHP14 may regulate actin remodeling directly and play an important role in dynamic regulation of the actin cytoskeleton. We observed a colocalization of PHP14 with Arp3 and F-actin at the leading edge of migrating cells. Moreover, PHP14 was recruited to the actin remodeling sites in parallel with Arp3 during lamellipodia formation. Furthermore, PHP14 knockdown impaired Arp3 localization at the leading edge of lamellipodia, as well as lamellipodia formation. Most importantly, we found that PHP14 was a novel F-actin-binding protein, displaying an Arp2/3-dependent localization to the leading edge. Collectively, our results indicated a crucial role for PHP14 in the dynamic regulation of the actin cytoskeleton and cell migration.